2020
DOI: 10.2174/1871523018666191111124028
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Radiation-induced Gastrointestinal System Injury using Resveratrol or Alpha-lipoic Acid: A Pilot Histopathological Study

Abstract: Aim: In this study, we aimed to determine possible mitigation of radiation-induced toxicities in the duodenum, jejunum and colon using post-exposure treatment with resveratrol and alpha-lipoic acid. Background: After the bone marrow, gastrointestinal system toxicity is the second critical cause of death following whole body exposure to radiation. Its side effects are responsible for reducing the quality of life of patients who had undergone radiotherapy. Resveratrol has an antioxidant effect and stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…An experiment confirmed that all such modulatory effects of resveratrol were able to alleviate radiation‐induced enteritis 192 . Another study demonstrated that protection of the intestine by resveratrol against apoptosis and necrosis induction following ionizing radiation ameliorated infiltration of leukocytes, reduced bleeding and alleviated chronic morphological changes in the duodenum, jejunum, ileum and colon 193 . Resveratrol has also been shown to attenuate secretion of inflammatory cytokines in the ileum and the liver following whole body irradiation 194 .…”
Section: Immunoregulatory Effects Of Resveratrol In Normal Tissuesmentioning
confidence: 80%
See 1 more Smart Citation
“…An experiment confirmed that all such modulatory effects of resveratrol were able to alleviate radiation‐induced enteritis 192 . Another study demonstrated that protection of the intestine by resveratrol against apoptosis and necrosis induction following ionizing radiation ameliorated infiltration of leukocytes, reduced bleeding and alleviated chronic morphological changes in the duodenum, jejunum, ileum and colon 193 . Resveratrol has also been shown to attenuate secretion of inflammatory cytokines in the ileum and the liver following whole body irradiation 194 .…”
Section: Immunoregulatory Effects Of Resveratrol In Normal Tissuesmentioning
confidence: 80%
“…192 Another study demonstrated that protection of the intestine by resveratrol against apoptosis and necrosis induction following ionizing radiation ameliorated infiltration of leukocytes, reduced bleeding and alleviated chronic morphological changes in the duodenum, jejunum, ileum and colon. 193 Resveratrol has also been shown to attenuate secretion of inflammatory cytokines in the ileum and the liver following whole body irradiation. 194 One of the important targets in the intestine for resveratrol is NLRP3/inflammasome, by inhibiting which, release of IL-1 in the intestine can be decreased by resveratrol.…”
Section: Pneumonitis and Pulmonary Fibrosismentioning
confidence: 99%
“…Several plant products alleviate the injurious effects of acute IR exposure, as demonstrated by a large number of investigations in various animal models using largely endpoints that measure either improved rates of survival or improved functions of specific organ systems. Some of these agents are Sea buckthorn (Hippophae rhamnoides-Hippophae) pulp, polyphenols, lycopene, resveratrol, caffeine, curcumin, and Ginkgo biloba extract [88][89][90][91][92][93][94][95].…”
Section: Other Promising Agents Under Developmentmentioning
confidence: 99%
“…Some studies have reported a number of various strategies to improve the radiotherapeutic efficacy or ameliorate the ionizing radiation-induced toxicity, including (1) the combination of radiation therapy with other cancer treatment modalities (e.g., surgery or chemotherapy), which the aim of the combined therapy is the enhancement of tumor cell sensitivity to radiation therapy [12,13]; (2) the use of advanced radiation therapy techniques (e.g., stereotactic radiosurgery, stereotactic radiotherapy, intensity-modulated radiation therapy, or image-guided radiation therapy) which can result in a more radiation dose to the tumor without an increase in the radiation dose to the surrounding normal organs [13]; and (3) the use of herbal and natural products as radioprotective and radiosensitizing agents for reducing the radiation therapy-induced toxicity [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%